Agrobacterium rhizogens mediated transformation of Ashwagandha (Withaniasomnifera (L) Dunal - Pareeth C M (Department of Plant Biotechnology, College of Agriculture, 2014)
The present study describes aseptic seed germination, establishment of shoot and normal root culture, Agrobacterium rhizogenes mediated transformation for hairy root culture, confirmation of transformation by PCR method and detection of rol A and rol B genes, phytochemcial assays of root cultures and roots derived from mature field grown plants for qualitative and quantitative analysis of total withanolide content, withaferin A and withanolide A of Withania somnifera (L.) Dunal. Half- strength MS medium with 0.5 mg/l GA3 were best to achieve maximum (93 %) seedlings rapidly. Multiple shoot culture was obtained by culturing the cotyledonary nodal explants in MS solid medium with 0.2 mg/l BAP and 0.05 mg/l IAA. Terminal shoot cuttings from shoot culture grown onto half- strength MS solid medium with 0.2 mg/l IBA were more efficient (98 % with 4-5 roots) in inducing healthy normal roots than both terminal and basal leaf segments. Hairy root culture was initiated by infecting cotyledons, hypocotyls leaf and internode explants with different wild type strains, A4, LBA 9402, and MTCC 532. The cotyledons infected with A. rhizogenes strain A4 induced hairy roots directly from the infected sites at a high frequency (90 %, 11.5 ± 0.2) than hypocotyl explants (12 %, 0.5 ± 0.05) which was best. The molecular evidence of rol A and rol C gene integration was confirmed by PCR amplification. Growth of the hairy root was measured by determining fresh weight and dry weight during time-course study in shake flask cultures. The maximum root biomass of hairy root culture (3.4 g) was noticed at 23rd day was more compared to normal root culture (2.6 g). Total withanolide content was more in transformed root culture (0.198 g) than normal root culture (0.103 g). The TLC analysis showed the compounds with same Rf values (0.36) and (0.59) as that of authentic samples of withaferin A and withanolide A respectively and it was confirmed again by Co-TLC. The HPLC analysis showed a more concentration of withaferin-A (22.3 mg/g dw) and withanolide A (2.35 mg/g dw) in hairy root culture than normal root culture (4.3 mg/g dw of withaferin-A and 1.65 mg/g dw of withanaloide-A).